The Transition From Hybrid Learning Model To In-Person Mandarin Language Learning Among Grade XI Social Science 5 Students of SMAN 6 Malang - Ester Emanuelawati; Desti Nur Aini; Lukluk Ul Muyassaroh (Journal of Chinese Language and Culture Studies, 2025)
The dynamics of the educational transition from online to offline learning continue to be a topic of discussion to this day. The educational conditions affected by the pandemic were experienced not only by students but also by teachers and schools from both social and emotional perspectives. The purpose of this study is to examine the implementation of hybrid learning during the COVID-19 pandemic and offline learning in the post-pandemic period, as well as to analyze the impact of the transition from online to offline learning after the pandemic. This study employed a qualitative descriptive research method. The data sources consisted of both primary and secondary data. The Miles and Huberman model was used as the data analysis technique in this research on learning transition. The study was conducted in Class XI Social Science 5 at SMAN 6 Malang, particularly in the Mandarin language class. The findings revealed that hybrid learning was carried out by combining online and offline systems simultaneously, emphasizing the use of a web-based Learning Management System (LMS) as a platform for documentation and distribution of educational content in schools. The transition from online to offline learning indicated a balanced level of self-efficacy among students. This outcome is categorized as positive, as students were able to manage their strengths and weaknesses effectively in completing school assignments.